Sonification of geometry - Hiew, Joey Mun Yee (Nanyang Technological University, 2021)
Computer graphics has become a core technology in many fields for displaying images using the aid of a computer. An important topic in computer graphics is visualisation, where abstract data is represented graphically. As datasets are evolving and becoming more complex, perceiving information using visualisation may become more difficult. Users are required to mentally project a 2-D projection to 3D in order to fully understand the nature of the geometry. To address this, researchers have developed 3D display technologies to help overcome this problem. However, the huge amount of data required pose a limitation to the use of 3D displays. Additional modalities like haptics were also explored to aid in understanding and perceptualization but physical limitations reduce the effectiveness of haptics. This project explores the use of sound as an additional modality to aid user’s understanding of the 3D geometric shape. A Unity3D application was developed to test the feasibility of sonifying the distance to the boundary of the geometric object to guide users to the boundary. A user study is conducted and responses were collected from a questionnaire, and its results and analysis are discussed in this report. This project shows that it is feasible to use sound as an additional modality to improve perception of 3D geometric objects